2020
DOI: 10.1371/journal.pone.0243467
|View full text |Cite
|
Sign up to set email alerts
|

Predicting self-harm within six months after initial presentation to youth mental health services: A machine learning study

Abstract: Background A priority for health services is to reduce self-harm in young people. Predicting self-harm is challenging due to their rarity and complexity, however this does not preclude the utility of prediction models to improve decision-making regarding a service response in terms of more detailed assessments and/or intervention. The aim of this study was to predict self-harm within six-months after initial presentation. Method The study included 1962 young people (12–30 years) presenting to youth mental he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 73 publications
(96 reference statements)
1
20
0
Order By: Relevance
“…The AUC-ROCs were 0.744–0.755 but the study was limited by sample size (n=1962 patients) and class imbalance (320 [16%] self-harm vs 1642 [84%] no self-harm). 24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AUC-ROCs were 0.744–0.755 but the study was limited by sample size (n=1962 patients) and class imbalance (320 [16%] self-harm vs 1642 [84%] no self-harm). 24…”
Section: Discussionmentioning
confidence: 99%
“…The AUC-ROCs were 0.744-0.755 but the study was limited by sample size (n=1962 patients) and class imbalance (320 [16%] self-harm vs 1642 [84%] no self-harm). 24 In this study we focused on the use of commissioning level data, but there has also been interest in using clinical text from electronic health-care records in the USA. Analysis of these records has yielded high accuracy but the approach is only applicable to hospitals that universally use electronic records, which is rare in the UK.…”
Section: Comparison To Existing Literaturementioning
confidence: 99%
“…Even at the early age of 9-10 years, 8.4% of 7,944 children interviewed in the US-based Adolescent Brain and Cognitive Development study reported having past or current suicide ideation and 1.3% confirmed attempted suicides (Janiri et al, 2020). Non-fatal self-harm and previous suicide attempts considerably increase the risk of subsequent suicide attempts (Beckmann et al, 2018;Geulayov et al, 2019;Iorfino et al, 2020), making it crucial to better understand the mechanisms leading to suicidal behaviors at an early age to prevent suicides. However, previous efforts to predict suicide were often unsatisfactory, mainly because effect sizes of individual factors that have been shown to correlate with suicidal behaviors were only small to moderate (Franklin et al, 2017).…”
Section: Predicting Suicide Attempts In Adolescents In the Longitudin...mentioning
confidence: 99%
“…The clinician should be aware of common factors predisposing to self-harm. In the recent Australian cohort study involving 1,962 individuals aged 12–30 years who visited a mental health clinic, researchers examined the predictors of within 6 months repeated self-harm ( 34 ). The three strongest predictors were a history of self-harm, younger age and social and occupational functioning measured by low value in the Social and Occupational Functioning Assessment Scale (SOFAS) ( 35 ).…”
Section: Factors Suggesting Further Evaluation Among Pilotsmentioning
confidence: 99%